Penggunaan Sufiks Hi, Ryou, dan Kin yang Bermakna ‘Biaya’ dalam Asahi & Yomiuri Shibun: Kajian Morfosemantik - Wibawa, Galih Mahesa; Rasiban, Linna Meilia; Bachri, Aep Saeful (Vocational College of Diponegoro University, 2024)
The suffixes kin, ryou, and hi have different kanji but the same meaning and usage, which often makes it difficult for Japanese learners to distinguish their use when writing Japanese sentences. Therefore, the purpose of this study is to find out how the formation process and the meaning and ability of these suffixes in substituting each other. The method used in this research is descriptive qualitative. The data sources are taken from Asahi Shibun and Yomiuri Shinbun newspapers published on March 24 to 28, 2023. Based on the analysis, it is found that the suffixes kin, ryou, and hi belong to the classification of compound words formed from content morpheme + setsuji. Based on the word class, they are categorized as kin'in hyouji suffixes, which are nouns that show currency. Based on the vocabulary classification, the suffix can be attached to wago, kango, and konshugo type words but cannot be attached to gairaigo. Based on their semantic objects, the suffix kin mean 'money' which has a definite monetary value, the suffix ryou means 'rate' which is to give or get something in return, and the suffix hi means 'cost' as it is to the word to which it is attached. Then based on the substitution results, from the 20 data found, only 7 data can replace each other in terms of kanji formation, and from the 7 data only 3 data can substitute each other in terms of meaning.